Pola Perilaku Personal Information Management Mahasiswa dalam Menggunakan Mendeley Reference Manager - Imaniar Putri Arifiyana; Yanuar Yoga Prasetyawan (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional, 2023)
ABSTRACT Students always deal with a variety of information to support their lecture activities, which often makes them trapped in a situation known as